Enhanced feedrate scheduling algorithm for CNC system with acceleration look-ahead and sin2 acceleration profile - Sun, Zheng; Wang, Xintian; Liu, Bin; Lu, Jiexin; Mei, Xuesong; Zhou, Yi (International journal of advanced manufacturing technology, 2022)
The smooth motion profile with less oscillation ensures the processing quality of machined parts. Meanwhile, keeping feedrate under its limit as high as possible can reduce the processing time and save cost. In this paper, a novel feedrate scheduling algorithm with acceleration lookahead is presented. Through the sin 2 acceleration profile, the continuity of jerk can be guaranteed. Based on the 4-phase profile, the look-ahead function is also extended for acceleration, which avoids the frequent changing of acceleration when scheduling short segments. On a designed benchmark, the effectiveness of the proposed algorithm is verified and compared with the state-of-the-art. The algorithm is implemented on a laser patterning machine with the galvanometric scanners as its feed drive system. The results confirm the effectiveness of the presented scheduling method.